1972
DOI: 10.1038/bjc.1972.66
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma in Uganda: Geographic and Ethnic Distribution

Abstract: Over the quinquennium 1964-68 the crude annual incidence of Kaposi's sarcoma in Uganda per million of the population was 7·9 overall, 14·6 for males and 1·1 for females. Statistical analysis indicates that the disease is most prevalent in highland areas to the west and among the indigenous Bantu tribes. There was no correlation with the distribution of squamous cell carcinoma of the lower leg, and Kaposi's sarcoma was not seen in an Indian or European during the period under review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Convergence zones are also marked at the east side of Lake Victoria (now Kenya and Tanzania), intermixing Bantu, Southern Nilotic and Eastern Nilotic populations. [18] showed greater standardized KSHV incidences in the western districts of Uganda.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Convergence zones are also marked at the east side of Lake Victoria (now Kenya and Tanzania), intermixing Bantu, Southern Nilotic and Eastern Nilotic populations. [18] showed greater standardized KSHV incidences in the western districts of Uganda.…”
mentioning
confidence: 90%
“…Third, Ugandan groups may differ in presenting KS. Two decades before the discovery of KSHV, Taylor et al [18] showed that KS incidence differed in Uganda by tribe and geographic area. The Sudanic tribes tended to have greater incidences than the Bantu, which in turn had greater incidences than the Nilotes.…”
mentioning
confidence: 99%
“…It is particularly frequent and aggressive when associated with infection by human immunodeficiency virus-1 (2), in contrast to classical KS, which is rare and indolent (2)(3)(4)(5). To date, the pathogenesis of KS is not completely understood, but in vivo and in vitro evidence indicates that this sarcoma probably develops from reactive, nontumoral cells (6, 7) that become characteristically "spindle"-shaped and induce angiogenesis when stimulated by a variety of cytokines and growth factors, including interleukin-1 and -6, interferon-␥, granulocyte-macrophage colony-stimulating factor, tumor necrosis factor-␣, fibroblast growth factors, plateletderived growth factor, chemokines, VEGF-A, transforming growth factors (reviewed in Ref.…”
Section: Ksmentioning
confidence: 99%
“…The early phase of disease is characterized by an infiltrate of leukocytes and a prominent angiogenesis, which is crucial to the growth and progression of KS (8)(9)(10)(11)(12). The current hypothesis to explain the behavior of KS is an imbalance in the network of soluble mediators caused by HIV-1, other viruses, immunosuppressive treatment, or genetic factors (13)(14)(15)(16)(17)(18). The tat transgenic mice develop lesions similar to KS ( 19), suggesting that this viral protein can be a factor which triggers the imbalance in the network of soluble mediators.…”
mentioning
confidence: 99%